KEPEMIMPINAN AGILE SEORANG KYAI DI PONDOK PESANTREN MODERN NURUSSALAM - Haerudin Haerudin; Ahmad Sukandar; Lim Wasliman; Rahma Dilla Zainuri; Mitra Sasmita (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Agile leadership is agile leadership in dealing with every problem that exists in an organization. So in this study, the aim is to find out how the Agile leadership of a kyai in the Nurussalam Modern Islamic boarding school is. The method used in this study is qualitative descriptive research with a case study design. Data collection was carried out through observation, in-depth interviews and participant recording. Data analysis is carried out using data reduction, data services and conclusion drawn. The validation test is checked for its credibility, transferability, reliability, and confirmation through data triangulation and informant review. The results of this study show that the agile leadership of seorng kayai in the Nurussalam Islamic Boarding School is shown by collaborating with a strong team, role models and motivators, innovating in developing Islamic boarding schools, being quick in making decisions, and collaborating with the community in developing Islamic boarding schools.